How to assess quality of life. Theoretical and methodological research aspects in cross-border regions - Angelovič Martin; Ištok Robert (Bulletin of Geography. Socio-Economic Series, 2016)
In our paper we deal with both the theoretical and methodological aspects of our research, which focuses on the quality of life in cross-border regions. The aim of the paper is to draw on the methodological system for assessment of the quality of life in those regions, taking into consideration both the objective and subjective dimension. The first part of the paper contains the use of qualitative methods when assessing the quality of life, which, in our understanding, are not sufficiently applied in the process of assessment of quality, not only in the field of Geography. We also focus on the definition of the key terms related to our work, such as ‘quality of life, border and border-region/neighbour’. The main emphasis of our work lies in the formulation of the theoretical and methodological model of the quality of life assessment in the cross-border regions. The methodological outline of researching this issue is presented in the chart. The scale of the region is a key element we take into consideration, since it is significant when choosing the appropriate method of life quality assessment. We also distinguish between the application of both the qualitative and quantitative research methods on various scales. In our opinion, the representation of the qualitative methods in research should increase with the increase in the scale of the area researched. In the conclusion we provide selected outcomes of our research at various scales, which confirm the validity of our theoretical basis, since we came to various findings, depending on the scales researched.